15/15 translocation in Prader-Willi syndrome. Issue 4 (August 1977) - Fraccaro, M; Zuffardi, O; Buhler, E M; Jurik, L P
Abstract : Two further cases (one previously published as D/D translocation) of 15/15 translocation in Prader-Willi syndrome are reported, which brings the total cases of this specific chromosomal anomaly in connection with this specific syndrome up to three or possibly four. It is suggested that Prader-Willi syndrome might be caused by loss of short arm material of chromosome 15.